Preliminary findings on the volatile oil obtained from the fresh leaves of Citron Citrus medica L. (Fam. Rutaceae) - Makapugay, Helena C.
The fresh leaves of Citrus medica L. was found to contain 0.3% essential oil and 74.5% moisture. The physical and chemical properties of the oil were determined.